Electronic media use and sleep in toddlerhood and preschool age - R. Praninskienė; R. Jusienė; I. Laurinaitytė; L. Petronytė; I. Rakickienė; V. Urbonas (Neurologijos seminarai)
Introduction and aim. The use of modern information technology (IT) can affect children’s physical and mental health. The aim of the present study was to find out how long young children use different IT devices (screens) and whether the IT usage was associated with sleep habits, routines, sleep duration and sleep problems. Methods. We analyzed data of 500 children, whose age was between 18-72 months (M=41.29, SD=15.44). Parents of toddlers and preschool children from different regions of Lithuania were asked to fill in questionnaires about their children’s mental and physical health and the use of information technologies and screen time on workdays and weekends. The study was carried out in April-August 2017. The survey questionnaire contained questions about the child’s development, social environment, and usage of IT devices. Children’s sleep problems were assessed using the Child’s Behavior Check list (CBCL /1½-5). Results. The study results revealed that most children’s sleep duration was 9-10 hours per night. 95.3% of children, who slept 8 hours, and all children, who slept 7 hours during night, slept also during daytime. 77% of children at this age slept during the day. Younger children had habits and routine before sleep time, but they had also more awakenings during the nighttime. About half of the children had at least one IT device in their sleeping room. Children of parents with lower education were more likely to have an IT device in the sleeping room, and they were permitted to watch movies before bedtime. Also, children who had an IT device in their sleeping room had more difficulties initiating sleep, and they had more sleep problems (reaching the borderline or clinical level). Children who were sleeping shorter than 8 hours at night were using computers longer during the week and on weekends, they also spent more time on other screens during the weekends. Finally, the longer over all screen time was prominent in the group of children who had the highest scores of sleep problems. Conclusions. This study supports recent findings in other countries confirming that the use of IT in the early childhood before going to sleep and having devices in bedroom are associated with sleep problems, difficulties initiating sleep and shorter sleep duration.